Front Cover: Plug&Play Fiber‐Coupled 73 kHz Single‐Photon Source Operating in the Telecom O‐Band (Adv. Quantum Technol. 6/2020). Issue 6 (9th June 2020) - Musiał, Anna; Żołnacz, Kinga; Srocka, Nicole; Kravets, Oleh; Große, Jan; Olszewski, Jacek; Poturaj, Krzysztof; Wójcik, Grzegorz; Mergo, Paweł; Dybka, Kamil; Dyrkacz, Mariusz; Dłubek, Michał; et al.
Abstract : The cover image presents the first stand‐alone telecom quantum light source launching single photons directly into a single‐mode optical fiber. It includes a semiconductor quantum dot (QD) which is excited by an integrated laser and cooled by compact Stirling cooler at 40 K. The advanced quantum device includes all filter elements to suppress intensive laser light and to direct single photons at a wavelength of 1.3 µm to the output. For further details see article number 2000018 by Stephan Reitzenstein and co‐workers.